(untitled) (Bangladesh Journal of Child Health, 2018)
Community-acquired pneumonia (CAP) is a potentially serious infection in children and often results in hospitalization.CAP symptoms are nonspecific in younger infants, but cough and tachypnea are usually present in older children. The diagnosis can be based on the history and physical examination results in children with fever plus respiratory signs and symptoms. Chest radiography and rapid viral testing may be helpful when the diagnosis is unclear. The most likely etiology depends on the age of the child. Viral and Streptococcus pneumonia infections are most common in preschoolaged children, whereas Mycoplasmapneumoniaeis common in older children.Most children can be managed empirically with oral antibiotics as outpatients without specific laboratory investigations.The decision to treat with antibiotics is challenging, especially with the increasing prevalence of viral and bacterial coinfections. Those with severe infections or with persistent or worsening symptoms need more intensive investigations and may need admission to hospital. The choice and dosage of antibiotics should be based on the age of the patient, severity of the pneumonia and knowledge of local antimicrobial resistance patterns. Bangladesh J Child Health 2018; VOL 42 (1) :38-42